Proper names in cognitive onomastics: Meaning and categorization of proper names - Reszegi, Katalin (2023)
This theoretical paper gives an overview about how proper names and different name types exist in the mental system, also showing new solutions provided by the cognitive perspective in connection with old questions of name theory. Cognitive onomastics is a relatively new approach to the study of proper names based on a cognitive approach to language. In this framework, names as linguistic elements are parts of the cognitive system, thus mental representation and usage of proper names can be described by general cognitive processes. The overview of topics and directions of cognitive onomastic research shows that studying names and naming in a cognitive framework has a lot of potential. Providing further evidence of the advantages of the cognitive approach, the paper discusses two controversial issues of name theory. First, the meaning of proper names is addressed from a cognitive perspective, pointing out the complex meaning matrix of this word class; then the categorization of proper names is discussed, i.e., how the networks and subnetworks of names emerge within the mental lexicon.